Comparative approach for trace metal risk evaluation in settling particles from the Uruguay River, Argentina: enrichment factors, sediment quality guidelines and metal speciation - Tatone, Leandro Martín (2016)
The source and potential risks of trace metals in settling material collected with sediment traps in the Uruguay River were evaluated utilizing enrichment factors (EF), sediment quality guidelines (SQG) and speciation using a 4-step sequential extraction procedure. The total organic carbon content of the settling material was relatively high and homogeneous (2.5 ± 0.3 %) and showed no correlation with the metal concentrations. Total trace metal concentrations decrease from Fe (48,969 ± 7380 µg g⁻¹), Mn (1859 ± 233 µg g⁻¹), Zn (84 ± 7.6 µg g⁻¹), Cu (56 ± 6.9 µg g⁻¹), Cr (19 ± 2.7 µg g⁻¹), Ni (16 ± 2.0 µg g⁻¹) and Pb (13 ± 1.2 µg g⁻¹). The average EF of Zn, Cr, Ni and Pb are below 1.5 indicating natural sources, whereas those of Cu and Mn are consistently higher (EF > 2) insinuating some anthropogenic influence. Consistently, Cu concentrations duplicated the SQG (35.7 μg g⁻¹) suggesting that adverse biological effects may be observed occasionally. However, speciation results revealed that most metals are associated with the residual fraction, strongly linked to the mineral matrix, and therefore unavailable to aquatic organisms. The sole exception is Mn which is mainly found in the non-residual fractions (∑F1 − F3 = 82 %). Trace metal mobility/bioavailability decreased from Mn (82 %) ≫ Pb (37 %) > Cr (26 %) ~ Ni (25 %) > Zn (20 %) > Cu (14 %) > Fe (10 %). These results demonstrate the utility of metal speciation studies to assess the real risk for aquatic organisms of high Cu concentrations, but associated to relatively immobile fractions of reduced bioavailability.